Konsep Solusi Keuangan Syariah Bagi Perusahaan Konstruksi Infrastruktur di Indonesia – Studi Kasus Konstruksi Jalan - Mohamad Torik Langlang Buana; Sofyan Halim (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2021)
The aim of this research is to write about the concept of akad that could be applied in provide solutions to financial needs of construction companies in infrastructure sector in Indonesia. The involvement of government in growing the construction industry of infrastructure sector is really increasing the economic aspect that would also increase the finance syariah. Construction work is unique, the period of works relatively limited, the work methods almost different. Some of construction companies rely on projects that are owned by the government such project of national road. The existence of syariah banking is relatively in long period in Indonesia, more than 25 years of operation. However, according to latest report by OJK, the contribution of syariah banking in construction industry is still relatively small, less than 8% compared to the financing by conventional bank. This research writes the concept of akad that are applicable to construction companies. The method used is library research by searching references that are related to syariah financing and infrastructure construction business, books, journals, prospectus of syariah banks and construction companies, and other sources.